A structural exposé of noncanonical molecular reactivity within the protein tyrosine phosphatase WPD loop - Wang, H; Perera, L; Jork, N; Riley, AM; Potter, BVL; Et al. (Nature Research, 2022)
Structural snapshots of protein/ligand complexes are a prerequisite for gaining atomic level insight into enzymatic reaction mechanisms. An important group of enzymes has been deprived of this analytical privilege: members of the protein tyrosine phosphatase (PTP) superfamily with catalytic WPD-loops lacking the indispensable general-acid/base within a tryptophan-proline-aspartate/glutamate context. Here, we provide the ligand/enzyme crystal complexes for one such PTP outlier: Arabidopsis thaliana Plant and Fungi Atypical Dual Specificity Phosphatase 1 (AtPFA-DSP1), herein unveiled as a regioselective and efficient phosphatase towards inositol pyrophosphate (PP-InsP) signaling molecules. Although the WPD loop is missing its canonical tripeptide motif, this structural element contributes to catalysis by assisting PP-InsP delivery into the catalytic pocket, for a choreographed exchange with phosphate reaction product. Subsequently, an intramolecular proton donation by PP-InsP substrate is posited to substitute functionally for the absent aspartate/glutamate general-acid. Overall, we expand mechanistic insight into adaptability of the conserved PTP structural elements.